Investigating population differentiation in a major African agricultural pest: evidence from geometric morphometrics and connectivity suggests high invasion potential - M. Karsten; P. Addison; B. Jansen van Vuuren; J. S. Terblanche (Molecular Ecology, 2016)
The distribution, spatial pattern and population dynamics of a species can be influenced by differences in the environment across its range. Spatial variation in climatic conditions can cause local populations to undergo disruptive selection and ultimately result in local adaptation. However, local adaptation can be constrained by gene flow and may favour resident individuals over migrants—both are factors critical to the assessment of invasion potential. The Natal fruit fly ( Ceratitis rosa ) is a major agricultural pest in Africa with a history of island invasions, although its range is largely restricted to south east Africa. Across Africa, C. rosa is genetically structured into two clusters (R1 and R2), with these clusters occurring sympatrically in the north of South Africa. The spatial distribution of these genotypic clusters remains unexamined despite their importance for understanding the pest's invasion potential. Here, C. rosa , sampled from 22 South African locations, were genotyped at 11 polymorphic microsatellite loci and assessed morphologically using geometric morphometric wing shape analyses to investigate patterns of population structure and determine connectedness of pest‐occupied sites. Our results show little to no intraspecific (population) differentiation, high population connectivity, high effective population sizes and only one morphological type (R2) within South Africa. The absence of the R1 morphotype at sites where it was previously found may be a consequence of differences in thermal niches of the two morphotypes. Overall, our results suggest high invasion potential of this species, that area‐wide pest management should be undertaken on a country‐wide scale, and that border control is critical to preventing further invasions.